Methotrexate Normalizes Up‐Regulated Folate Pathway Genes in Rheumatoid Arthritis. Issue 11 (28th October 2013) - Blits, Marjolein; Jansen, Gerrit; Assaraf, Yehuda G.; van de Wiel, Mark A.; Lems, Willem F.; Nurmohamed, Mike T.; van Schaardenburg, Dirkjan; Voskuyl, Alexandre E.; Wolbink, Gert‐Jan; Vosslamber, Saskia; Verweij, Cornelis L.
<x xml:space="preserve">Abstract</x> Objective The folate antagonist methotrexate (MTX) is an anchor drug in the treatment of rheumatoid arthritis (RA), but its mechanism of action with regard to the impact on folate metabolism remains elusive. The aim of the present study was to investigate the cellular pharmacologic impact of MTX on peripheral blood cells, by comparing MTX‐treated RA patients to MTX‐naive RA patients and healthy controls. Methods Gene expression microarray data were used to investigate the expression of 17 folate pathway genes by peripheral blood cells from a cohort of 25 RA patients treated with MTX, 10 MTX‐naive RA patients starting treatment with MTX, and 15 healthy controls (test cohort). Multiplex real‐time polymerase chain reaction was used to validate the results in an independent cohort, consisting of 151 RA patients treated with MTX, 28 MTX‐naive RA patients starting treatment with MTX, and 24 healthy controls (validation cohort). Results Multiple folate metabolism–related genes were consistently and significantly altered between the 3 groups in both cohorts. Concurrent with evidence of an immune‐activation gene signature in MTX‐naive RA patients, significant up‐regulation of the folate‐metabolizing enzymes γ‐glutamyl hydrolase and dihydrofolate reductase, as well as the MTX/folate efflux transporters ABCC2 and ABCC5, was observed in the MTX‐naive RA group compared to healthy controls. Strikingly, MTX treatment of RA patients normalized these differential gene expression levels to the levels observed in healthy controls. Conclusion These results suggest that under inflammatory conditions, basal folate metabolism in the peripheral blood cells of RA patients is markedly up‐regulated, and treatment with MTX restores folate metabolism to normal levels. Identification of this novel gene signature provides insight into the mechanism of action of MTX, thus paving the way for development of novel folate metabolism–targeted therapies.